2010
DOI: 10.1186/1477-7827-8-50
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunctions in patients with diabetes: a study from Iran

Abstract: BackgroundDiabetes mellitus is a chronic disease that causes short and long-term complications. This study aimed to investigate the prevalence of sexual dysfunctions (SD) among diabetic patients in Iran and to examine whether glycemic control has a role in SD.MethodsA consecutive sample of diabetic women and men who were registered in the Isfahan Endocrine and Metabolism Center, Iran were studied. Sexual dysfunction was evaluated using the Female Sexual Function Index (FSFI) in women and the International Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 38 publications
(47 reference statements)
11
63
2
Order By: Relevance
“…(19) Furthermore, Al-Turki (30) reported that 21.4% of diabetic male patients less than 40 years old had partial ED in comparison to 75.3% incidence in patients between 40 and 60 years old. 30 This association between age and ED confirms what has been shown in Khatib et al (20) and Marumo et al (33) However, Ziaei-Rad et al (15) did not find any significant statistical relationship between age and SD in both genders. Regarding the duration of diabetes and its effect on ED among men and its severity, there was a significant association between them which has been clearly stated in other studies.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…(19) Furthermore, Al-Turki (30) reported that 21.4% of diabetic male patients less than 40 years old had partial ED in comparison to 75.3% incidence in patients between 40 and 60 years old. 30 This association between age and ED confirms what has been shown in Khatib et al (20) and Marumo et al (33) However, Ziaei-Rad et al (15) did not find any significant statistical relationship between age and SD in both genders. Regarding the duration of diabetes and its effect on ED among men and its severity, there was a significant association between them which has been clearly stated in other studies.…”
Section: Resultssupporting
confidence: 71%
“…In Giuliano FA et al study, (26) ED was reported in 67% of the patients with diabetes alone. In addition, Selvin & Burnett (32) reported that the prevalence of ED was 51.3% in men with diabetes in the U.S. A study from Iran Ziaei-Rad et al (15) found that 77% of diabetic Iranian men have ED.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[19] The epidemiological studies on sexual attitudes and sexual difficulties are common in a middle-aged female worldwide and it should be ranged between 40-60%. [20] In Type 1 DM about 71% prevalence exists and www.wjpps.com Vol 6, Issue 9, 2017. 686…”
Section: Prevalencementioning
confidence: 99%